2001
DOI: 10.1089/089771501317095304
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xLExpression after Contusion to the Rat Spinal Cord

Abstract: After contusion-derived spinal cord injury, (SCI) there is localized tissue disruption and energy failure that results in early necrosis and delayed apoptosis, events that contribute to chronic central pain in a majority of patients. We assessed the extent of contusion-induced apoptosis of neurons in a known central pain-signaling pathway, the spinothalamic tract (STT), which may be a contributor to SCI-induced pain. We observed the loss of STT cells and localized increase of DNA fragmentation and cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…Groups of rats were subjected to SCI using the NYU Impactor (see Materials and Methods), and the molecular signatures of apoptosis were examined 24 h after contusion. In agreement with previous reports (Qiu et al, 2001;Nesic-Taylor et al, 2005), we found that SCI decreased Bcl-x L mRNA (Fig. 4 A) and protein (Fig.…”
Section: Methylprednisolone Inhibits Sci-induced Apoptosissupporting
confidence: 94%
“…Groups of rats were subjected to SCI using the NYU Impactor (see Materials and Methods), and the molecular signatures of apoptosis were examined 24 h after contusion. In agreement with previous reports (Qiu et al, 2001;Nesic-Taylor et al, 2005), we found that SCI decreased Bcl-x L mRNA (Fig. 4 A) and protein (Fig.…”
Section: Methylprednisolone Inhibits Sci-induced Apoptosissupporting
confidence: 94%
“…Vehicle-treated injured spinal cords showed significant increases in cytosolic oligonucleosomes when compared to sham rats treated with vehicle (Fig. 2), in agreement with our earlier reports Qiu et al, 2001;Nesic-Taylor et al, 2005) that showed that significant apoptotic cell death occurs during the first 24 h after injury. As expected, Tat-Bcl-x L treatment significantly decreased levels of cytosolic oligonucleosomes, confirming the anti-apoptotic effectiveness of Tat-Bcl-x L .…”
Section: Anti-apoptotic Effects Of Tat-bcl-x Lsupporting
confidence: 92%
“…The Bcl-2 family of proteins, containing pro-apoptotic (Bax, Bad, Bid) and anti-apoptotic (Bcl-2, Bcl-x L ) members, is central to the regulation of both caspase-dependent and caspase-independent apoptosis, by modulating mitochondrial outer membrane permeability (Tsujimoto, 2003;Sharpe et al, 2004). Among the Bcl-2 family, Bcl-x L is the principal anti-apoptotic member in the postnatal and adult central nervous system (Gonzalez-Garcia et al, 1994;Gonzalez-Garcia et al, 1995;Alonso et al, 1997;Parsadanian et al, 1998); where it is highly expressed in neurons and oligodendrocytes in the rat spinal cord (Qiu et al, 2001;Nesic-Taylor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF may exerts this neuroprotective effects through calmodulin [48,49]. BDNF may also be involved in the suppression of injury-induced delayed apoptosis [50], possibly through the increase of the antiapoptotic molecule, Bcl-xl [51]. An alternative mechanism for the neuroprotective effect of BDNF could be a BDNFregulated reduction of the number of terminal clubs formed at the distal axonal stumps in the rostral cord [52].…”
Section: Discussionmentioning
confidence: 99%